2015
DOI: 10.5194/bg-12-3819-2015
|View full text |Cite
|
Sign up to set email alerts
|

The stable isotopic composition of <i>Daphnia</i> ephippia reflects changes in δ<sup>13</sup>C and δ<sup>18</sup>O values of food and water

Abstract: Abstract. The stable isotopic composition of fossil resting eggs (ephippia) of Daphnia spp. is being used to reconstruct past environmental conditions in lake ecosystems. However, the underlying assumption that the stable isotopic composition of the ephippia reflects the stable isotopic composition of the parent Daphnia, of their diet and of the environmental water have yet to be confirmed in a controlled experimental setting. We performed experiments with Daphnia pulicaria cultures, which included a control t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 53 publications
1
35
1
Order By: Relevance
“…Our findings of D 15 N estimates also confirmed that any temperature effects on D 15 N values for aquatic consumers are not straightforward. Indeed, findings from other aquatic organisms suggested a general trend of decreasing D 15 N values with increasing temperature (Power et al, 2003;Barnes et al, 2007), whereas other studies reported an opposite trend (Schilder et al, 2015;Masclaux & Richoux, 2017). In our study, temperature effects on D 13 C followed different patterns when calculated with fresh or altered isotopic baselines, and with or without larval lipid normalization.…”
Section: Food Isotopic Integrity In Rearing Experimentscontrasting
confidence: 51%
See 2 more Smart Citations
“…Our findings of D 15 N estimates also confirmed that any temperature effects on D 15 N values for aquatic consumers are not straightforward. Indeed, findings from other aquatic organisms suggested a general trend of decreasing D 15 N values with increasing temperature (Power et al, 2003;Barnes et al, 2007), whereas other studies reported an opposite trend (Schilder et al, 2015;Masclaux & Richoux, 2017). In our study, temperature effects on D 13 C followed different patterns when calculated with fresh or altered isotopic baselines, and with or without larval lipid normalization.…”
Section: Food Isotopic Integrity In Rearing Experimentscontrasting
confidence: 51%
“…5%, they also reported contradictory and unclear relationships with temperature. While Power et al (2003) and Masclaux & Richoux (2017) reported increase in D 13 C values with increasing temperature, Schilder et al (2015) found the opposite relationships, and they found similar contradicting observations for D 15 N. A range of confounding factors could explain this lack of consistency among studies (Masclaux & Richoux, 2017). For example, lipids exhibit lower d 13 C values than other constituents (protein) in animal tissues (DeNiro & Epstein, 1977), and a lipid normalization of larval d 13 C values could be required to get more reliable data interpretations (McConnaughey & McRoy, 1979;Smyntek et al, 2007).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Further elegant experiments have shown that the stable isotopic composition of Daphnia ephippia provides information on that of the parent Daphnia, and of the food and water they were exposed to during formation. Schilder et al (2015b) demonstrated that there were only small offsets between Daphnia and ephippia relative to the range of variation in Daphnia stable isotopic composition reported from down-core studies. Interestingly however, their work also indicated that temperature may have a minor influence on the δ 13 C, δ 15 N, and δ 18 O values of Daphnia body tissue and ephippia which has implications for water temperature reconstruction work using oxygen isotopes, as well as highlighting the care with which controlled feeding experiments need to be conducted (sensu Perga and Grey, 2010).…”
Section: Looking Back: Hindcastingmentioning
confidence: 76%
“…Only 10% of the oxygen in chitin from aquatic crustaceans is derived from food (Nielson and Bowen, 2010), while the dietary contribution of O to human hair protein was estimated to be ∼8% , although that study may have underestimated the atomic routing of O from diet to hair keratin. This implies that changes in δ 18 O values of environmental and body water are the main drivers of the tissue O isotopic composition variability Wang et al, 2009;Nielson and Bowen, 2010;Soto et al, 2013c;Schilder et al, 2015; but see cautions for feline carnioves, Pietsch et al, 2011), and that little trophic information is obtained by using δ 18 O values.…”
Section: Tools For Analysismentioning
confidence: 99%